Water stress assessment of cork oak leaves and maritime pine needles based on LIF spectra - Lavrov, a; Utkin, a B.; Marques da Silva, J.; Vilar, Rui; Santos, N. M.; Alves, B. (Optics and Spectroscopy, 2012)
The aim of the present work was to develop a method for the remote assessment of the impact of fire and drought stress on Mediterranean forest species such as the cork oak (Quercus suber) and maritime pine (Pinus pinaster). The proposed method is based on laser induced fluorescence (LIF): chlorophyll fluo rescence is remotely excited by frequencydoubled YAG:Nd laser radiation pulses and collected and analyzed using a telescope and a gated high sensitivity spectrometer. The plant health criterion used is based on the I685 /I740 ratio value, calculated from the fluorescence spectra. The method was benchmarked by comparing the results achieved with those obtained by conventional, continuous excitation fluorometric method and water loss gravimetric measurements. The results obtained with both methods show a strong correlation between them and with the weightloss measurements, showing that the proposed method is suitable for fire and drought impact assessment on these two species
Keywords: Cork oak; laser induced fluorescence (LIF); maritime pine (voyant); water stress